Assessing job-housing balance among low-income households in Penang Island, Malaysia - Hafizah Rosli; Mohd Azmeer Abu Bakar; Mohamad Pirdaus Yusoh; Normah Abdul Latip; Kasim Mansor (Malaysia Institute of Planners, 2024)
The balance between the geographical proximity of job and housing locations will have a significant impact on commuting patterns to the workplace. The key determinants for attaining job-housing equilibrium are the geographic placement, proximity, and travel time between an individual's domicile and place of employment. The absence of a balance between employment availability and housing can significantly harm the quality of life and overall welfare of those in low-income categories. The objective of this study is to assess the balance between work and residential areas for economically disadvantaged households in two distinct districts on Penang Island, Malaysia. A quantitative methodology employed to choose 306 respondents from low-income groups in the northeast and southwest areas to complete the questionnaire. The binary logistic regression analysis indicated that, despite the diverse economic sectors and distinct land uses and built environments, the job-housing balance in both the northeast and southwest areas is comparable. The study revealed that the transport system is the crucial factor in addressing the disparity between job opportunities and affordable housing for low-income individuals. In order to enhance their job accessibility, they require transportation that is both cost-effective, highly efficient, and sufficiently suitable. Hence, policymakers ought to intensify their strategies to ensure the provision of adequate, cost-effective, and proficient transport infrastructures to cater to the needs of this specific demographic across various geographical settings.